2020
DOI: 10.1186/s12879-020-05154-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and CT findings of COVID-19: differences among three age groups

Abstract: Background The novel coronavirus pneumonia (coronavirus disease 2019, COVID-19) has spread around the world. We aimed to recapitulate the clinical and CT imaging features of COVID-19 and their differences in three age groups. Methods The clinical and CT data of patients with COVID-19 (n = 307) that had been divided into three groups (Group 1: < 40 years old; Group 2: 40 ≤ age < 60 years old; Group 3: ≥ 60 years old) according to age were analyzed retrospectively. Results Of all patients, 114 (37.1%) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 30 publications
1
30
0
1
Order By: Relevance
“…Still, the link between older individuals and the likelihood to develop severe and critical cases of COVID-19 has been made before, either due to immunosenescence, malnutrition, or ignoring more easily the early symptoms and consequently missing the best time to seek medical advice [ 20 , 21 ]. Furthermore, several studies registered an important association between increased age and COVID-19 severity/fatality [ 22 , 23 , 24 , 25 , 26 ]. The vulnerability of elderly individuals is illustrated in recent studies.…”
Section: Discussionmentioning
confidence: 99%
“…Still, the link between older individuals and the likelihood to develop severe and critical cases of COVID-19 has been made before, either due to immunosenescence, malnutrition, or ignoring more easily the early symptoms and consequently missing the best time to seek medical advice [ 20 , 21 ]. Furthermore, several studies registered an important association between increased age and COVID-19 severity/fatality [ 22 , 23 , 24 , 25 , 26 ]. The vulnerability of elderly individuals is illustrated in recent studies.…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, influenza-like illness (ILI) includes patients with severe respiratory symptoms, community-acquired pneumonia, fever, acute respiratory illness, and similar septic syndromes [ 32 ]. COVID-19 cases include patients with acute symptoms suggestive of COVID-19 infection [ 33 ]. An ILI/COVID group was created as some symptoms are common to the two categories.…”
Section: Methodsmentioning
confidence: 99%
“…The results demonstrated the obvious infectivity of this disease and the importance of isolation [9]. A previously study [10] found that patients with underlying diseases are more likely to develop severe COVID-19. A recent study [11] showed that the occurrence of COPD was associated with a nearly four-fold higher risk of developing severe COVID-19.…”
Section: Discussionmentioning
confidence: 52%
“…Imaging revealed more lesions in the 40-65 and > 65-year-old groups (P < 0.0001). The days after the nucleic acid detection turned negative in the three age groups were: 9.19 ± 3.93 (< 40), 10.04 ± 4.10 (40-65), and 13.57 ± 2.76 (> 65) (P = 0.0373). After antiviral treatment, together with antiinfection regimen if the patient with lung infection and continuous oxygen inhalation if the patient is hypoxic, all patients achieved total recovery and were discharged with follow-up.…”
mentioning
confidence: 91%